In-medium Υ suppression and feed-down in UU and PbPb collisions - Hölck, Johannes; Nendzig, Felix; Wolschin, Georg (Physical review, 2017)
The suppression of Υ mesons in the hot quark-gluon plasma (QGP) versus reduced feed-down is investigated in UU collisions at energies currently available at the BNL Relativistic Heavy Ion Collider and PbPb collisions at energies available at the CERN Large Hadron Collider. Our centrality- and pT-dependent model encompasses screening, collisional damping, and gluodissociation in the QGP. For Υ(1S) it is in agreement with data from both STAR and CMS collaborations provided the relativistic Doppler effect and the reduced feed-down from the Υ(nS) and χb(nP) states are properly considered. At both energies, most of the Υ(1S) suppression is found to be due to reduced feed-down, whereas most of the Υ(2S) suppression is caused by hot-medium effects. The importance of the latter increases with energy. The pT dependence is flat due to the relativistic Doppler effect and reduced feed-down. We predict the Υ(1S) suppression in PbPb at √sNN=5.02TeV.